2017
DOI: 10.3390/s17071612
|View full text |Cite
|
Sign up to set email alerts
|

Candle Soot Coating for Latent Fingermark Enhancement on Various Surfaces

Abstract: We demonstrate a facile method termed candle soot coating (CSC) for fast developing latent fingermarks (LFMs) on various kinds of surfaces (glass, ceramic, metal, paper and adhesive tape). The CSC method can be considered as simple, fast, and low-cost as well as providing high contrast for LFM visualization in potential forensic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“… self-triggered alarm system using a triboelectric nanosensor and nitrocellulose membrane as substrate for fingermarks upon contact [ 533 ]; sulfonated poly (diphenylacetylene) polymer in solution interacting with sweat components and exhibiting a “turn-on” emission mode [ 534 ]; PDMS support covered by a PDA thin film then applied on a fingermark: transfer of PDA into sweat and ridge pattern visualization through PDA-catalysed electroless silver deposition (positive image on the substrate, negative image on the PDMS support) [ 535 ]; follow-up of the above study: PDMS support covered by a PDA thin film and a silver layer then applied on a fingermark to allow optical detection and Raman chemical imaging [ 473 ]; CTF-developed fingermarks combined with transmission-/reflection-mode multiwavelength digital holography [ 536 ]; use of an AIE-based tetraphenylethene-based dye [ 537 ], conjugated polyelectrolyte [ 538 ], diphenylpyrimidinone derivatives [ 539 ] or acridinediones [ 540 ] to detect sebum-rich marks on various substrates; p-C1-PDPA film taking advantage of swelling-induced emission enhancement to detect sebum-rich marks on non-porous substrates [ 541 ]; two-step detection of sebum-rich fingermarks involving the lifting of secretion residue by a hydrophilic cellulose membrane followed by dye staining of the membrane (the sebum-rich secretions acting as a mask) [ 542 ] (note: this study has been further reported by Ref. [ 543 ]); use of paraffin candle soot to detect sebum-rich fingermarks on various substrates [ 544 ]; two-step detection of sebum-rich fingermarks involving the lipophilic adsorption of nitric oxide (NO) followed by the application of 1,2-diaminoanthraquinone [ 545 ]; sublimation of lanthanide complexes to detect fingermarks on non-porous substrates [ 546 ]; use of lysozyme-binding aptamers combined with a lanthanide-based carboxymethyl nanocellulose hydrogel [ 547 ] or embedded in two DNA strands with a G-quadruplex/NMM complex [ 548 ] to detect (fresh sebum-rich) fingermarks on various substrates; use of electrolytes in aqueous solutions to detect marks on various substrates [ 549 ]; two-step detection of fingermarks involving the transfer of secretion residue to a nanofibrillated cellulose membrane doped with fluorescent C-dots, followed by CA fuming and dye-staining (using super-paramagnetic iron oxide NPs; application mode not specified) [ 550 ]; ...…”
Section: Fingermark Composition and Detectionmentioning
confidence: 99%
“… self-triggered alarm system using a triboelectric nanosensor and nitrocellulose membrane as substrate for fingermarks upon contact [ 533 ]; sulfonated poly (diphenylacetylene) polymer in solution interacting with sweat components and exhibiting a “turn-on” emission mode [ 534 ]; PDMS support covered by a PDA thin film then applied on a fingermark: transfer of PDA into sweat and ridge pattern visualization through PDA-catalysed electroless silver deposition (positive image on the substrate, negative image on the PDMS support) [ 535 ]; follow-up of the above study: PDMS support covered by a PDA thin film and a silver layer then applied on a fingermark to allow optical detection and Raman chemical imaging [ 473 ]; CTF-developed fingermarks combined with transmission-/reflection-mode multiwavelength digital holography [ 536 ]; use of an AIE-based tetraphenylethene-based dye [ 537 ], conjugated polyelectrolyte [ 538 ], diphenylpyrimidinone derivatives [ 539 ] or acridinediones [ 540 ] to detect sebum-rich marks on various substrates; p-C1-PDPA film taking advantage of swelling-induced emission enhancement to detect sebum-rich marks on non-porous substrates [ 541 ]; two-step detection of sebum-rich fingermarks involving the lifting of secretion residue by a hydrophilic cellulose membrane followed by dye staining of the membrane (the sebum-rich secretions acting as a mask) [ 542 ] (note: this study has been further reported by Ref. [ 543 ]); use of paraffin candle soot to detect sebum-rich fingermarks on various substrates [ 544 ]; two-step detection of sebum-rich fingermarks involving the lipophilic adsorption of nitric oxide (NO) followed by the application of 1,2-diaminoanthraquinone [ 545 ]; sublimation of lanthanide complexes to detect fingermarks on non-porous substrates [ 546 ]; use of lysozyme-binding aptamers combined with a lanthanide-based carboxymethyl nanocellulose hydrogel [ 547 ] or embedded in two DNA strands with a G-quadruplex/NMM complex [ 548 ] to detect (fresh sebum-rich) fingermarks on various substrates; use of electrolytes in aqueous solutions to detect marks on various substrates [ 549 ]; two-step detection of fingermarks involving the transfer of secretion residue to a nanofibrillated cellulose membrane doped with fluorescent C-dots, followed by CA fuming and dye-staining (using super-paramagnetic iron oxide NPs; application mode not specified) [ 550 ]; ...…”
Section: Fingermark Composition and Detectionmentioning
confidence: 99%
“…In another study, Zhang et al [9] reported that the structure of the prepared coatings with the nanoparticle of CS coated on Al alloy substrate has revealed a porous network. Using different substrates including metallic, glass, ceramic, and adhesive paper, Wei et al [31] also reported a similar nanonetwork structure of CS material when coated for a period of 10-20 s. In terms of the CS coating's thickness, Wu et al [30] manipulated the thickness of the deposited CS material by altering the deposition time. Esmeryan et al [7] reported nanonetwork CS particles with sizes around ~50 nm when it was coated on the glass substrate using the epoxy resin and glow discharge RF plasma.…”
Section: Resultsmentioning
confidence: 97%
“…Somit lässt sich nachvollziehen, warum nach dem Abspülen des Spurenträgers solch klare und kontrastreiche Fingerabdrücke zurückbleiben. Rasterelektronenmikroskopische (REM) Aufnahmen hatten zudem gezeigt, dass die Erhebungen des Abdrucks im Unterschied zum Untergrund mit ziemlich stabilen Rußschichten überdeckt sind [7], was ebenfalls auf starke zwischenmolekulare Wechselwirkungen am Ort der Spur schließen lässt.…”
Section: Diskussionunclassified
“…Dabei ist uns in der jüngeren Literatur eine verfahrenstechnisch sehr einfache Methode aufgefallen, bei der die Visualisierung von Fingerabdrücken über einer Kerzenflamme gelingt. Das Verfahren eignet sich zudem für praktisch alle Oberflächenmaterialien, ist einfach durchzuführen [7] und darum aus didaktischer Perspektive eine interessante Methode für den schulischen Chemieunterricht, die hier näher vorgestellt werden soll.…”
Section: Introductionunclassified